Idiopathic sudden sensorineural hearing loss and tinnitus: The role of hyperbaric oxygen therapy - Magalhães, Clara (2014)
Introduction: The etiopathogenic mechanism of Idiopathic Sudden Sensorineural Hearing Loss (ISSHL) remain unclear. Vascular event or viral infection theories had been suggested. In any case, HBO provides a better cochlear oxygenation and cellular viability after acute lesion.Material and methods: The authors present a retrospective study of the patients with ISSHL who started HBO in Pedro Hispano Hospital (2006-2011). The protocol included 20 sessions with 100% oxygen in hyperbaric chamber at 2,5 atm and for 90 minutes. For analysis we used software SPSS 17.0, with a 0,05 level of significance. We reviewed 347 cases.Results: The average time from complaints until the beginning of HBO was 15,8 days. After failure with corticotherapy and the introduction with HBO we had a hearing recovery of 20 dB, using SRT (Speech Reception Threshold), and the intensity of tinnitus reduced 1,6 points on visual analog scale.Conclusions: This study indicates a statistically significant improvement on audiometric recovery and intensity of tinnitus with use of HBO as salvage therapy.